2023
DOI: 10.5897/ijbc2022.1568
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting the diversity of the rhizosphere mycobiome of five native West African trees

I. Tchan Kassim,
Armel Olou Boris,
Basile Hounwanou Gbètondji
et al.

Abstract: Soil microbial communities play a vital role in ecosystem functioning by enhancing mineral nutrition and protecting forest trees against pathogens through mycorrhizal symbiosis. However, knowledge of the diversity and assemblage of belowground fungal communities associated with native host trees in tropical Africa is incomplete. Using high-throughput sequencing, this study examined soil fungal communities in the rhizosphere of five ectomycorrhizal trees (EcM) from (5) countries using ITS and LSU regions. Uncon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…). In a similar study by Tchan et al (2023), they found that soil fungal communities were host specific (P = 0.001). Basidiomycota were more frequently observed in the rhizosphere of Fabaceae, except for I. doka, whereas Ascomycota are more abundant in the rhizosphere of Phyllanthaceae (U. togoensis) and Dipterocarpaceae (M. kerstingii).…”
Section: Results and Results And Results And Results And Discussion D...mentioning
confidence: 77%
“…). In a similar study by Tchan et al (2023), they found that soil fungal communities were host specific (P = 0.001). Basidiomycota were more frequently observed in the rhizosphere of Fabaceae, except for I. doka, whereas Ascomycota are more abundant in the rhizosphere of Phyllanthaceae (U. togoensis) and Dipterocarpaceae (M. kerstingii).…”
Section: Results and Results And Results And Results And Discussion D...mentioning
confidence: 77%